Shielding composite material based on PPS (polyphenylene sulfite) composite carbon nanotubes as well as preparation method and application of shielding composite material
By accurately control the reaction conditions and the addition of additives during the aggregation reaction process, prepare a PPS composite carbon nanotuba -based shielding composite material with excellent mechanical properties and electromagnetic shielding performance, solving the performance of existing materials in the application of vehicle battery shell applications Insufficient issues.
Patent Information
- Application Number
- CN202411924016.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing shielding composite materials of PPS composite carbon nanotubes have problems such as poor mechanical properties, flame retardancy and poor electromagnetic shielding performance in vehicle-mounted battery shell applications.
By precisely controlling the construction and conditions of the reaction system during the polymerization reaction, including determining the amount of NMP, the order and amount of addition of additives, as well as nitrogen replacement, heating rate and time, a PPS composite carbon nanotube-based shield with excellent performance was prepared composite materials.
It has achieved a comprehensive improvement in the material's high temperature resistance, chemical corrosion resistance, good mechanical properties and good electromagnetic shielding performance, and is suitable for the production of protective casings for automotive batteries.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of production of shielding composite materials of PPS composite carbon nanotubes, in particular to a shielding composite material based on PPS composite carbon nanotubes and a preparation method and application thereof. Background Art
[0002] PPS (polyphenylene sulfide) is a high-performance thermoplastic resin with excellent high temperature resistance, corrosion resistance, mechanical properties, etc. Carbon nanotubes have good electrical properties, such as high conductivity, etc. The composite of PPS and carbon nanotubes to prepare shielding composite materials can combine the advantages of both to obtain materials with good electromagnetic shielding properties.
[0003] The existing PPS composite carbon nanotube shielding composite materials have problems of weak mechanical properties, poor flame retardancy and electromagnetic shielding performance in actual use. Especially in the field of vehicle battery shells. Because batteries, as the energy source of new energy vehicles, will generate complex electromagnetic fields during the charging and discharging process. On the one hand, the electromagnetic field radiated outward may interfere with other electronic equipment such as the radio and navigation system on the vehicle, affecting their normal operation; on the other hand, if there is a strong electromagnetic field in the outside world, it may also affect the internal circuits such as the battery management system, thereby affecting the performance and life of the battery, and may even cause safety problems. Summary of the invention
[0004] In view of the above deficiencies in the prior art, the purpose of the present invention is to provide a shielding composite material based on PPS composite carbon nanotubes, which has the advantages of high temperature resistance, chemical corrosion resistance, good mechanical properties, and good electromagnetic shielding performance, and is suitable for the production of protective casings for automotive batteries.
[0005] Another object of the present invention is to provide a method for preparing a shielding composite material based on PPS composite carbon nanotubes. During the polymerization reaction, the construction of the reaction system (such as determination of the amount of NMP used, the order and amount of additive addition) and the reaction conditions (such as nitrogen replacement, heating rate and time) are precisely controlled, which is beneficial to improving the selectivity of the reaction and the quality of the product, and greatly improving the product performance.
[0006] The third purpose of the present invention is to provide an application of a shielding composite material based on PPS composite carbon nanotubes, which is used for protective casing of automotive batteries and has good thermal conductivity, excellent mechanical properties, outstanding chemical corrosion resistance, high flame retardancy, excellent electrical insulation performance and high electromagnetic shielding properties; the solution blending method, extrusion granulation, injection molding and other processes adopted are all relatively mature polymer material processing methods, which are easy to operate and control, can ensure the stability and consistency of product quality, and are conducive to large-scale production.
[0007] The present invention is achieved by adopting the following technical solutions: The method for preparing the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) adding the acidified carbon nanotubes into the distilled purified NMP solvent, the mass concentration of the carbon nanotubes being 0.9-1.2%; then ultrasonically dispersing the carbon nanotubes, the ultrasonic power being 250-350 W, the ultrasonic time being 50-75 min, so that the carbon nanotubes form a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication is used; (2) Under stirring conditions, slowly add the PPS product to the NMP dispersion of carbon nanotubes. After the addition is completed, continue to stir the reaction in an oil bath at 75-80°C for 4-6 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 600-1200 rpm. Pour the evenly mixed solution into a pre-prepared mold, place it in a vacuum oven at 95-105°C and dry it for 16-20 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0008] The weight average molecular weight of the PPS product is 35,000-38,000, the degree of polymerization is 135-165, and the crystallinity is 35-45%; the mass of the carbon nanotubes is 4-7% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 0.5-1 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.02-0.05 MPa for 8-10 hours, and then drying at 0.08-0.1 MPa for 8-10 hours.
[0009] The surface of the acidified carbon nanotubes carries functional groups such as carboxyl, which can physically adsorb or chemically react (such as acid-base reaction, hydrogen bonding, etc.) with the active sites on the PPS molecular chain (such as end groups, functional groups on side chains, etc.). When PPS is dissolved in NMP and mixed with carbon nanotubes, the carbon nanotubes can be evenly dispersed in the PPS solution. After drying and forming, the carbon nanotubes can effectively enhance the mechanical properties and electrical conductivity of PPS. At the same time, the presence of PPS also provides a stable matrix for carbon nanotubes to prevent carbon nanotubes from agglomerating. The two cooperate with each other to form a composite material with excellent performance. NMP plays a dual role of dissolving PPS and dispersing carbon nanotubes in the solution blending stage. For PPS, NMP can destroy the interaction between PPS molecular chains, making it fully dissolved, and providing good conditions for uniform mixing with carbon nanotubes. For carbon nanotubes, NMP can be wrapped on the surface of carbon nanotubes through solvation, reducing the van der Waals force between carbon nanotubes, so that it can be stably dispersed in the solution. In addition, the boiling point of NMP is relatively high, and it can be gradually removed by controlling the temperature and vacuum degree in the subsequent drying process, which is conducive to the formation of a uniform composite material structure.
[0010] In the step (1), the acid treatment step of the carbon nanotubes is: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (2.5-3.0):1, and prepare 165-185 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 3 to 5 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration are repeatedly washed with deionized water until the pH value of the filtrate is neutral to remove the residual acid; the washed carbon nanotubes are dried in a vacuum oven at 65 to 75° C. for 18 to 20 hours to obtain acidified carbon nanotubes.
[0011] Concentrated sulfuric acid has strong oxidizing and dehydrating properties, and concentrated nitric acid is also a strong oxidant. After the two are mixed, the dehydrating property of concentrated sulfuric acid can make some carbon atoms on the surface of carbon nanotubes more susceptible to oxidation. The nitrate ions (NO 3 ⁻) In an acidic environment (concentrated sulfuric acid provides a large number of hydrogen ions), it has stronger oxidizing properties and can undergo redox reactions with carbon atoms on the surface of carbon nanotubes. This synergistic oxidation allows functional groups such as carboxyl to be more effectively introduced onto the surface of carbon nanotubes. At the same time, the heat released during the dilution process of concentrated sulfuric acid also helps to increase the reaction rate.
[0012] In the step (2), the preparation steps of the PPS product are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.08-0.1 MPa, and then nitrogen was introduced to 0.1-0.2 MPa, and this was repeated 3-5 times. Then, NMP solvent was added and stirring was started at a speed of 350-450 rpm. The stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 185-210°C at a rate of 1-2°C / min, keep reacting for 7-9h, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ is added dropwise to the ethanol precipitant, the dropping speed is controlled at 1 to 2 mL / s, and the low-speed stirring is adopted at 50 to 100 rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ are first washed 2 to 3 times with an aqueous solution containing 0.2 to 0.3% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed 5 to 8 times with deionized water to obtain PPS; the washed PPS is dried in a vacuum drying oven at 110 to 115° C. to constant weight to obtain a pure PPS product.
[0013] The purity of the p-dichlorobenzene is above 99.5%, and the moisture content is lower than 0.05%; the purity of the anhydrous sodium sulfide is above 95%, and the molar ratio of the anhydrous sodium sulfide to p-dichlorobenzene is (1.05-1.15):1.
[0014] The amount of triethylamine used is 0.3% to 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.15% to 0.25% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.6% to 0.8% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.06% to 0.08% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.15% to 0.25% of the mass of p-dichlorobenzene; and the amount of NMP used is such that the total concentration of each substance in the reaction system is maintained at 38% to 43%.
[0015] p-Dichlorobenzene provides the skeleton structure of the polymerization reaction and is the key monomer for generating the main chain of PPS. The sulfide ions in anhydrous sodium sulfide act as nucleophiles and undergo nucleophilic substitution reactions with the chlorine atoms on the p-dichlorobenzene molecules. The two react according to a molar ratio (1.05-1.15), ensuring that sufficient sodium sulfide participates in the reaction, so that the polymerization reaction can proceed fully and generate PPS molecular chains of sufficient length. Anhydrous sodium phosphate, as the main catalyst, can provide the initial catalytic active center to promote the reaction between p-dichlorobenzene and anhydrous sodium sulfide. As a co-catalyst, yttrium oxide can interact with anhydrous sodium phosphate due to its unique electronic structure and chemical properties. It may change the electron cloud distribution of anhydrous sodium phosphate, further optimize the structure of the catalytic active center, make the reaction substrate easier to adsorb and activate, thereby increasing the reaction rate and selectivity, and jointly promoting the efficient synthesis of PPS. The synergistic effect of the two can reduce the activation energy of the reaction, so that the reaction can proceed smoothly under relatively low temperature and pressure conditions, which not only accelerates the reaction rate, but also reduces the occurrence of side reactions, improves the synthesis efficiency of PPS and the quality performance of the product, such as more uniform molecular weight distribution and more regular molecular chain structure. Tetrabutylammonium bromide can transfer organic reactants such as p-dichlorobenzene from the organic phase to the aqueous phase or other reactive phases, so that it can be more fully contacted with inorganic reactants such as anhydrous sodium sulfide, thereby improving the collision probability and reaction efficiency of the reaction. At the same time, anhydrous sodium phosphate can better play its catalytic role in the aqueous phase or other active phases, further promoting the polymerization reaction. The two complement each other and jointly promote the reaction to the direction of generating PPS. After triethylamine neutralizes the acidic substance, the generated salt substance may produce a certain synergistic effect with anhydrous sodium phosphate, further affecting the ionic strength and polarity of the reaction system, which is conducive to the dissolution and diffusion of the reactants, thereby promoting the polymerization reaction of p-dichlorobenzene and anhydrous sodium sulfide, and improving the yield and quality of PPS. The intermediate formed by tetrabutylammonium bromide may interact with yttrium oxide, enhancing the stability and reactivity of the intermediate and making it easier to react with other reactants. This interaction further enhances the synergistic catalytic effect of the catalyst, accelerates the reaction rate, and promotes the synthesis of PPS. The synergistic effect of yttrium oxide and triethylamine may affect the growth and structure of the PPS molecular chain, so that the generated PPS has better comprehensive properties such as thermal stability and mechanical properties. For example, the adjustment of pH by triethylamine may affect the terminal groups of the PPS molecular chain, while the active center optimized by yttrium oxide may make the structure of the PPS molecular chain more regular. The two work together to improve the performance of PPS. Tetrabutylammonium bromide improves the reaction selectivity, and triethylamine adjusts the pH of the reaction system. The two work together to reduce the occurrence of side reactions and improve the purity and quality of PPS. At the same time, their synergistic effect may also affect the molecular structure and properties of PPS, such as improving the solubility and processing properties of PPS, making it more suitable for practical applications.
[0016] The shielding composite material based on PPS composite carbon nanotubes is prepared by the preparation method of the shielding composite material based on PPS composite carbon nanotubes described above.
[0017] The application of the shielding composite material based on PPS composite carbon nanotubes is used for protective shells for automobile batteries.
[0018] The method for preparing the protective shell for the automobile battery comprises the following steps: a. Add the dried silica, aluminum hydroxide, zinc stannate, zinc borate, glass fiber, magnesium oxide, boron nitride, TPE, polytetrafluoroethylene powder and PPS composite carbon nanotube-based shielding composite material to a high-speed mixer, first stir at 350-450 rpm for 2-3 min to make the materials preliminarily mixed, then gradually increase the speed to 900-1100 rpm, and continue stirring for 5-10 min; then, add antioxidant 1010, antioxidant 1076, light stabilizer 770, light stabilizer 944 and anti-hydrolysis agent to the above mixture, and stir at a speed of 550-780 rpm for 3-5 min; b. Take silane coupling agent KH550, dilute it with ethanol, add it to the conductive carbon black, and ultrasonically treat it in an ultrasonic device for 25 to 30 minutes to make the silane coupling agent evenly coat the conductive carbon black. Then add it to the mixer and continue stirring for 2 to 3 minutes. Reduce the stirring speed to 650 to 800 rpm; then add zinc stearate and silicone oil, stir at a speed of 450 to 650 rpm for 2 to 3 minutes to make the materials more evenly mixed.
[0019] c. Add the mixed materials into a twin-screw extruder for extrusion granulation. The temperature of the extruder is set to 200°C, 245-260°C, 260-285°C, 285-300°C, 300-325°C, 325-340°C from the feeding section to the die. The screw speed is 195-225rpm. The extruded materials are air-cooled and then pelletized to obtain composite material particles. d. Dry the composite material particles in an oven at 85-95°C for 2-4 hours, and then add them to an injection molding machine for injection molding to make a protective shell for automotive batteries; the injection molding temperature is 285-310°C, the injection molding pressure is 90-110 MPa, the holding time is 12-16 seconds, the cooling time is 22-30 seconds, and the temperature of the mold is controlled at 45-55°C.
[0020] Before preparing the protective casing for automotive batteries, the raw materials need to be pretreated: Silica, aluminum hydroxide, zinc stannate, zinc borate, and glass fiber: Dry in an oven at 100 to 120°C for 2 to 4 hours to remove moisture and prevent it from affecting material properties.
[0021] TPE (thermoplastic elastomer): If it is in granular form, it can be used directly; if it is in block form, preheat it at 60-80°C to soften it, then cut it into small pieces for later use.
[0022] Magnesium oxide: Dry in an oven at 100-120°C for 2-4 hours to remove moisture.
[0023] Boron nitride: Ball milling is performed to reduce particle size, increase specific surface area, and improve its dispersibility in the matrix.
[0024] In the preparation method of the protective shell for automobile batteries, the weight percentages of the raw materials used are: shielding composite material based on PPS composite carbon nanotubes: 50-70 parts; silicon dioxide: 3-5 parts; aluminum hydroxide: 5-8 parts; zinc stannate: 3-5 parts; zinc borate: 3-5 parts; TPE: 3-8 parts; antioxidant 1010: 0.3-0.8 parts; antioxidant 1076: 0.2-0.7 parts; light stabilizer The stabilizer 770 is 0.3 to 0.8 parts; the light stabilizer 944 is 0.2 to 0.7 parts; the conductive carbon black is 2 to 3 parts; the glass fiber is 3 to 5 parts; the anti-hydrolysis agent is 0.5 to 1 parts; the polytetrafluoroethylene powder is 1 to 3 parts; the zinc stearate is 0.5 to 1.5 parts; the silicone oil is 0.5 to 1 parts; the silane coupling agent KH550 is 0.5 to 1.5 parts; the magnesium oxide is 8 to 10 parts; the boron nitride is 5 to 8 parts. The anti-hydrolysis agent is a carbodiimide anti-hydrolysis agent, preferably polycarbodiimide Stabaxol~P.
[0025] Both magnesium oxide and boron nitride have good thermal conductivity. Magnesium oxide can play a role in increasing the heat conduction path in the material. The high thermal conductivity of boron nitride can cooperate with magnesium oxide to build a more efficient three-dimensional thermal conductive network, so that heat can be quickly transferred in the material, effectively improving the thermal conductivity of the material, and helping the protective shell for automotive batteries to dissipate heat during operation and prevent local overheating. Both have good stability at high temperatures. In the high temperature environment that the car charging pile may face, it can maintain its own stable performance, not decompose or deform, and jointly maintain the structural integrity and performance stability of the material to ensure the long-term use of the protective shell for automotive batteries. Aluminum hydroxide, zinc stannate and zinc borate are effective flame retardants. When aluminum hydroxide is decomposed by heat, it absorbs a lot of heat and releases water vapor, which plays a role in diluting combustible gases; zinc stannate can form a dense oxide protective film during the combustion process to prevent oxygen from contacting combustible substances; zinc borate releases crystal water at high temperatures, absorbs heat and forms a glassy borate covering layer, which plays a role in heat insulation and preventing combustion. Silicon dioxide can be filled inside the material during the combustion process to form an isolation layer, reducing heat transfer and the diffusion of combustible gases. Glass fiber can prevent the spread of flames to a certain extent, and enhance the structural strength of the material, making it difficult for the material to collapse during the combustion process, maintaining the integrity of the material, and thus jointly improving the flame retardant properties of the material. Glass fiber has high strength and modulus, which can significantly improve the mechanical properties of the material. Silicon dioxide can be filled in the gaps of the material, increasing the density of the material, and synergistically enhancing the hardness and compressive strength of the material with glass fiber. At the same time, the combination of these inorganic fillers and the matrix material can enable the material to effectively transfer stress between the filler and the matrix when subjected to external force, thereby improving the impact resistance and overall mechanical properties of the material.
[0026] The carbon nanotubes in the shielding composite material based on PPS composite carbon nanotubes can improve the interface properties of the material. Carbon nanotubes have a high specific surface area and good adsorption properties, and can form strong physical adsorption or chemical bonding with inorganic fillers (such as glass fiber, magnesium oxide, etc.), and enhance the interface bonding force between the inorganic filler and the PPS matrix. In this way, when the material is subjected to external force, the inorganic filler can better transfer stress and improve the comprehensive mechanical properties of the material. At the same time, in terms of thermal conductivity, it is also conducive to the transfer of heat between the filler and the matrix, and improves the thermal conductivity of the material. PPS itself has good electrical insulation properties, chemical corrosion resistance and certain mechanical properties. After combining with inorganic fillers, the high thermal conductivity, flame retardancy and reinforcement properties of inorganic fillers can make up for the shortcomings of PPS in these aspects, so that the comprehensive performance of the material is improved, and the requirements for various properties of the protective shell for automotive batteries are met. The carbon nanotubes and conductive carbon black in the shielding composite material based on PPS composite carbon nanotubes can jointly construct a conductive network. Carbon nanotubes themselves have good electrical conductivity. Conductive carbon black can be filled in the gaps between carbon nanotubes to increase the density of the conductive path, reduce the resistivity of the material, and improve the conductive performance of the material, thereby effectively improving the electromagnetic shielding performance of the material, so that the protective shell for automotive batteries can better resist external electromagnetic interference and prevent internal electromagnetic radiation leakage. TPE has good flexibility and elasticity, which can improve the toughness of the shielding composite material based on PPS composite carbon nanotubes, so that it can absorb more energy when impacted and reduce the brittle fracture of the material. At the same time, the addition of TPE can reduce the melt viscosity of the material, improve the processing fluidity of the material, make it easier to fill the mold during injection molding and other processing processes, and improve the appearance quality and molding accuracy of the product.
[0027] Antioxidants 1010 and 1076 can capture free radicals generated during the processing and use of materials, inhibit the occurrence of oxidation reactions, and prevent the aging and performance degradation of materials. Light stabilizers 770 and 944 can absorb light energy such as ultraviolet rays, convert it into harmless heat energy, and prevent the occurrence of photooxidation reactions. They work together to protect materials from different angles, effectively improve the weather resistance of materials, and ensure that the protective shell for automotive batteries can resist the effects of oxidation and light aging during long-term outdoor use, and maintain good appearance and performance. Anti-hydrolysis agents can prevent materials from hydrolyzing in humid environments. In the case where the car charging pile may be exposed to rain or high humidity environments, the anti-hydrolysis agent works in synergy with other raw materials to protect the chemical structure of the material, especially for the PPS matrix and some additives that may react with water, such as certain ester additives, etc., to maintain its stability, ensure that the performance of the material is not affected by hydrolysis, and extend the service life of the material. Silane coupling agent KH550 is used to improve the interface bonding between glass fiber and matrix and the dispersion of conductive carbon black. For glass fiber, KH550 can react with the hydroxyl groups on the surface of glass fiber and form chemical bonds with the PPS matrix, thereby enhancing the bonding force between glass fiber and matrix and improving the mechanical properties of the material. For conductive carbon black, KH550 can be coated on the surface of conductive carbon black to reduce its surface energy, making it easier to disperse in the matrix and prevent agglomeration, thereby better exerting the conductive and electromagnetic shielding properties of conductive carbon black. Zinc stearate and silicone oil both have lubricating effects. During the processing of materials, they can reduce the friction between the material and the processing equipment (such as screws, molds, etc.), making it easier for the material to flow and demold in the equipment. Zinc stearate mainly plays an internal lubricating role, while silicone oil has both internal and external lubricating effects. The synergistic effect of the two can effectively improve the processing performance of the material, improve the surface quality of the product, and reduce surface defects of the product, such as scratches and strains.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The shielding composite material based on PPS composite carbon nanotubes prepared by the present invention has the advantages of high temperature resistance, chemical corrosion resistance, good mechanical properties, and good electromagnetic shielding performance, and is suitable for the production of protective shells for automobile batteries.
[0029] (2) The method for preparing the shielding composite material based on PPS composite carbon nanotubes provided by the present invention accurately controls the construction of the reaction system (such as the determination of the amount of NMP used, the order and amount of adding additives) and the reaction conditions during the polymerization reaction, which is beneficial to improving the selectivity of the reaction and the quality of the product, thereby greatly improving the product performance.
[0030] (3) The shielding composite material based on PPS composite carbon nanotubes provided by the present invention is used for protective casing of automobile batteries and has good thermal conductivity, excellent mechanical properties, outstanding chemical corrosion resistance, high flame retardancy, excellent electrical insulation performance and high electromagnetic shielding properties; the solution blending method, extrusion granulation, injection molding and other processes adopted are all relatively mature polymer material processing methods, which are easy to operate and control, can ensure the stability and consistency of product quality, and are conducive to large-scale production. DETAILED DESCRIPTION
[0031] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0032] Example 1 The acid treatment steps of carbon nanotubes are: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.8:1, and use 170 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 4 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration were repeatedly washed with deionized water until the pH value of the filtrate was neutral to remove the residual acid; the washed carbon nanotubes were dried in a vacuum oven at 70° C. for 20 h to obtain acidified carbon nanotubes.
[0033] The preparation steps of PPS products are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.09MPa, and then nitrogen was introduced to 0.2MPa, and this was repeated 4 times. Then, NMP solvent was added, and stirring was started at a speed of 400rpm, and the stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 200°C at a rate of 2°C / min, keep reacting for 8 hours, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ was added dropwise to the ethanol precipitant, the dropping speed was controlled at 2mL / s, and the low-speed stirring was adopted at 80rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ were first washed three times with an aqueous solution containing 0.3% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed six times with deionized water to obtain PPS; the washed PPS was dried in a vacuum drying oven at 113°C to constant weight to obtain a pure PPS product.
[0034] Among them, the purity of p-dichlorobenzene is 99.6%, and the moisture content is 0.04%; the purity of anhydrous sodium sulfide is above 96%, and the molar ratio of anhydrous sodium sulfide to p-dichlorobenzene is 1.1:1. The amount of triethylamine used is 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.2% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.7% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.07% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.2% of the mass of p-dichlorobenzene; the amount of NMP used is to keep the total concentration of each substance in the reaction system at 40%.
[0035] The preparation method of the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) The acidified carbon nanotubes were added into the distilled purified NMP solvent, and the mass concentration of the carbon nanotubes was 1.1%; then, the carbon nanotubes were ultrasonically dispersed, with an ultrasonic power of 300 W and an ultrasonic time of 65 min, so that the carbon nanotubes formed a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication was used; (2) Under stirring conditions, the PPS product is slowly added to the NMP dispersion of carbon nanotubes. After the addition is completed, the reaction is continued to stir in a 78°C oil bath for 5 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 900 rpm. The evenly mixed solution is poured into a pre-prepared mold, placed in a vacuum oven and dried at 100°C for 18 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0036] The weight average molecular weight of the PPS product is 36,000, the degree of polymerization is 146, and the crystallinity is 40%; the mass of the carbon nanotubes is 5% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 0.8 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.04 MPa for 9 hours, and then drying at 0.09 MPa for 9 hours.
[0037] Example 2 The acid treatment steps of carbon nanotubes are: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3.0:1, and use 185 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 5 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration were repeatedly washed with deionized water until the pH value of the filtrate was neutral to remove the residual acid; the washed carbon nanotubes were dried in a vacuum oven at 75° C. for 20 h to obtain acidified carbon nanotubes.
[0038] The preparation steps of PPS products are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.1MPa, and then nitrogen was introduced to 0.2MPa, and this was repeated 5 times. Then, NMP solvent was added and stirring was started at a speed of 450rpm. The stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 210°C at a rate of 2°C / min, keep reacting for 9 hours, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ was added dropwise to the ethanol precipitant, the dropping speed was controlled at 2mL / s, and the low-speed stirring was adopted at 100rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ were first washed three times with an aqueous solution containing 0.3% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed eight times with deionized water to obtain PPS; the washed PPS was dried in a vacuum drying oven at 115°C to constant weight to obtain a pure PPS product.
[0039] Among them, the purity of p-dichlorobenzene is above 99.7%, and the moisture content is 0.04%; the purity of anhydrous sodium sulfide is 97%, and the molar ratio of anhydrous sodium sulfide to p-dichlorobenzene is 1.15:1. The amount of triethylamine used is 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.25% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.8% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.08% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.25% of the mass of p-dichlorobenzene; and the amount of NMP used is to keep the total concentration of each substance in the reaction system at 43%.
[0040] The preparation method of the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) The acidified carbon nanotubes were added into the distilled purified NMP solvent, with the mass concentration of carbon nanotubes being 0.9%; then, ultrasonic dispersion was performed, with the ultrasonic power of 250 W and the ultrasonic time of 50 min, so that the carbon nanotubes formed a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication was used; (2) Under stirring conditions, the PPS product is slowly added to the NMP dispersion of carbon nanotubes. After the addition is completed, the reaction is continued to stir in a 75°C oil bath for 4 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 600 rpm. The evenly mixed solution is poured into a pre-prepared mold, placed in a vacuum oven and dried at 95°C for 16 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0041] The weight average molecular weight of the PPS product is 35,000, the degree of polymerization is 135, and the crystallinity is 35%; the mass of the carbon nanotubes is 4% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 0.5 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.02 MPa for 8 hours, and then drying at 0.08 MPa for 8 hours.
[0042] Example 3 The acid treatment steps of carbon nanotubes are: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.5:1, and use 165 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 3 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration were repeatedly washed with deionized water until the pH value of the filtrate was neutral to remove the residual acid; the washed carbon nanotubes were dried in a vacuum oven at 65° C. for 18 h to obtain acidified carbon nanotubes.
[0043] The preparation steps of PPS products are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.08MPa, and then nitrogen was introduced to 0.1MPa, and this was repeated three times. Then, NMP solvent was added and stirring was started at a speed of 350rpm. The stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 185°C at a rate of 1°C / min, keep reacting for 7h, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ was added dropwise to the ethanol precipitant, the dropping speed was controlled at 1 mL / s, and the low-speed stirring was adopted at 50 rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ were first washed twice with an aqueous solution containing 0.2% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed five times with deionized water to obtain PPS; the washed PPS was dried in a vacuum drying oven at 110°C to constant weight to obtain a pure PPS product.
[0044] Among them, the purity of p-dichlorobenzene is 99.6%, and the moisture content is 0.05%; the purity of anhydrous sodium sulfide is 96%, and the molar ratio of anhydrous sodium sulfide to p-dichlorobenzene is 1.05:1. The amount of triethylamine used is 0.3% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.15% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.6% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.06% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.15% of the mass of p-dichlorobenzene; the amount of NMP used is to keep the total concentration of each substance in the reaction system at 38%.
[0045] The preparation method of the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) The acidified carbon nanotubes were added into the distilled purified NMP solvent, with the mass concentration of carbon nanotubes being 1.2%; then, they were ultrasonically dispersed at an ultrasonic power of 350 W and an ultrasonic time of 75 min, so that the carbon nanotubes formed a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication was used; (2) Under stirring conditions, the PPS product is slowly added to the NMP dispersion of carbon nanotubes. After the addition is completed, the reaction is continued to stir in an 80°C oil bath for 6 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 1200 rpm. The evenly mixed solution is poured into a pre-prepared mold, placed in a vacuum oven and dried at 105°C for 20 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0046] The weight average molecular weight of the PPS product is 38,000, the degree of polymerization is 165, and the crystallinity is 45%; the mass of the carbon nanotubes is 7% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 1 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.05 MPa for 10 hours, and then drying at 0.1 MPa for 10 hours.
[0047] Example 4 The acid treatment steps of carbon nanotubes are: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.8:1, and use 170 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 4 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration were repeatedly washed with deionized water until the pH value of the filtrate was neutral to remove the residual acid; the washed carbon nanotubes were dried in a vacuum oven at 70° C. for 20 h to obtain acidified carbon nanotubes.
[0048] The preparation steps of PPS products are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.09MPa, and then nitrogen was introduced to 0.2MPa, and this was repeated 4 times. Then, NMP solvent was added, and stirring was started at a speed of 400rpm, and the stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 200°C at a rate of 2°C / min, keep reacting for 8 hours, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ was added dropwise to the ethanol precipitant, the dropping speed was controlled at 2mL / s, and the low-speed stirring was adopted at 80rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ were first washed three times with an aqueous solution containing 0.3% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed six times with deionized water to obtain PPS; the washed PPS was dried in a vacuum drying oven at 113°C to constant weight to obtain a pure PPS product.
[0049] Among them, the purity of p-dichlorobenzene is 99.6%, and the moisture content is 0.04%; the purity of anhydrous sodium sulfide is above 96%, and the molar ratio of anhydrous sodium sulfide to p-dichlorobenzene is 1.1:1. The amount of triethylamine used is 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.2% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.7% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.07% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.2% of the mass of p-dichlorobenzene; the amount of NMP used is to keep the total concentration of each substance in the reaction system at 40%.
[0050] The preparation method of the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) The acidified carbon nanotubes were added into the distilled purified NMP solvent, with the mass concentration of carbon nanotubes being 1.2%; then, they were ultrasonically dispersed at an ultrasonic power of 350 W and an ultrasonic time of 75 min, so that the carbon nanotubes formed a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication was used; (2) Under stirring conditions, the PPS product is slowly added to the NMP dispersion of carbon nanotubes. After the addition is completed, the reaction is continued to stir in an 80°C oil bath for 6 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 1200 rpm. The evenly mixed solution is poured into a pre-prepared mold, placed in a vacuum oven and dried at 105°C for 20 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0051] The weight average molecular weight of the PPS product is 38,000, the degree of polymerization is 165, and the crystallinity is 45%; the mass of the carbon nanotubes is 7% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 1 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.05 MPa for 10 hours, and then drying at 0.1 MPa for 10 hours.
[0052] Example 5 The acid treatment steps of carbon nanotubes are: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3.0:1, and use 185 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 5 hours to allow the carbon nanotubes to fully contact with the mixed acid to undergo an oxidation reaction and introduce functional groups such as carboxyl groups on their surfaces; after the reaction is completed, slowly pour the reaction solution into a large amount of deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration were repeatedly washed with deionized water until the pH value of the filtrate was neutral to remove the residual acid; the washed carbon nanotubes were dried in a vacuum oven at 75° C. for 20 h to obtain acidified carbon nanotubes.
[0053] The preparation steps of PPS products are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.1MPa, and then nitrogen was introduced to 0.2MPa, and this was repeated 5 times. Then, NMP solvent was added and stirring was started at a speed of 450rpm. The stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 210°C at a rate of 2°C / min, keep reacting for 9 hours, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ was added dropwise to the ethanol precipitant, the dropping speed was controlled at 2mL / s, and the low-speed stirring was adopted at 100rpm to precipitate PPS to form larger precipitate particles; Ⅳ. The precipitated particles obtained in step Ⅲ were first washed three times with an aqueous solution containing 0.3% by mass of disodium ethylenediaminetetraacetate, and then repeatedly washed eight times with deionized water to obtain PPS; the washed PPS was dried in a vacuum drying oven at 115°C to constant weight to obtain a pure PPS product.
[0054] Among them, the purity of p-dichlorobenzene is above 99.7%, and the moisture content is 0.04%; the purity of anhydrous sodium sulfide is 97%, and the molar ratio of anhydrous sodium sulfide to p-dichlorobenzene is 1.15:1. The amount of triethylamine used is 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.25% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.8% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.08% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.25% of the mass of p-dichlorobenzene; and the amount of NMP used is to keep the total concentration of each substance in the reaction system at 43%.
[0055] The preparation method of the shielding composite material based on PPS composite carbon nanotubes comprises the following steps: (1) The acidified carbon nanotubes were added into the distilled purified NMP solvent, and the mass concentration of the carbon nanotubes was 1.1%; then, the carbon nanotubes were ultrasonically dispersed, with an ultrasonic power of 300 W and an ultrasonic time of 65 min, so that the carbon nanotubes formed a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication was used; (2) Under stirring conditions, the PPS product is slowly added to the NMP dispersion of carbon nanotubes. After the addition is completed, the reaction is continued to stir in a 78°C oil bath for 5 hours to allow the PPS to be fully dissolved and evenly mixed with the carbon nanotubes. The stirring speed is 900 rpm. The evenly mixed solution is poured into a pre-prepared mold, placed in a vacuum oven and dried at 100°C for 18 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
[0056] The weight average molecular weight of the PPS product is 36,000, the degree of polymerization is 146, and the crystallinity is 40%; the mass of the carbon nanotubes is 5% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 0.8 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.04 MPa for 9 hours, and then drying at 0.09 MPa for 9 hours.
[0057] Comparative Example 1 Compared with Example 1, the difference is that the carbon nanotubes are not subjected to acid treatment.
[0058] Comparative Example 2 Compared with Example 1, the difference is that, in the preparation process of the PPS product, yttrium oxide and tetrabutylammonium bromide are not added.
[0059] Comparative Example 3 Compared with Example 1, the differences are that, in the preparation process of the PPS product, no sulfonate is added; intermittent ultrasound is not used; and gradient vacuum is not used in the drying process.
[0060] Application Example 1 Pretreatment of raw materials: Silica, aluminum hydroxide, zinc stannate, zinc borate, and glass fiber: Dry in an oven at 110°C for 3 hours to remove moisture and prevent it from affecting material properties.
[0061] TPE (thermoplastic elastomer): If it is in granular form, it can be used directly; if it is in block form, preheat it at 70°C to soften it, then cut it into small pieces for later use.
[0062] Magnesium oxide: Dry in an oven at 110°C for 3 h to remove moisture.
[0063] Boron nitride: Ball milling is performed to reduce particle size, increase specific surface area, and improve its dispersibility in the matrix.
[0064] The method for preparing the protective shell for the automobile battery comprises the following steps: a. Add the dried silica, aluminum hydroxide, zinc stannate, zinc borate, glass fiber, magnesium oxide, boron nitride, TPE, polytetrafluoroethylene powder and the shielding composite material based on PPS composite carbon nanotubes obtained in Example 1 to a high-speed mixer, stir at 400 rpm for 3 min to make the materials preliminarily mixed, then gradually increase the speed to 1000 rpm and continue stirring for 8 min; then, add antioxidant 1010, antioxidant 1076, light stabilizer 770, light stabilizer 944 and anti-hydrolysis agent to the above mixture, stir at 680 rpm for 4 min; b. Take silane coupling agent KH550, dilute it with ethanol, add it to the conductive carbon black, and ultrasonically treat it in an ultrasonic device for 28 minutes to make the silane coupling agent evenly coat the conductive carbon black. Then add it to the mixer and continue stirring for 3 minutes. Reduce the stirring speed to 720rpm; then add zinc stearate and silicone oil, stir at a speed of 520rpm for 3 minutes to make the materials mix more evenly.
[0065] c. The mixed materials were added into a twin-screw extruder for extrusion granulation. The temperatures of the extruder were set to 200°C, 255°C, 275°C, 295°C, 315°C, and 330°C from the feeding section to the die head, and the screw speed was 210 rpm. The extruded materials were air-cooled and pelletized to obtain composite material particles. d. The composite material particles were dried in an oven at 90°C for 3 hours and then added to an injection molding machine for injection molding to form a protective casing for automotive batteries; the injection molding temperature was 300°C, the injection molding pressure was 100 MPa, the holding time was 14 seconds, the cooling time was 26 seconds, and the mold temperature was controlled at 50°C.
[0066] Among them, the mass parts of each raw material used are: shielding composite material based on PPS composite carbon nanotubes: 60 parts; silicon dioxide: 4 parts; aluminum hydroxide: 7 parts; zinc stannate: 4 parts; zinc borate: 4 parts; TPE: 5 parts; antioxidant 1010: 0.5 parts; antioxidant 1076: 0.5 parts; light stabilizer 770: 0.5 parts; light stabilizer 944: 0.5 parts; conductive carbon black: 3 parts; glass fiber: 4 parts; polycarbodiimide Stabaxol~P: 0.8 parts; polytetrafluoroethylene powder: 2 parts; zinc stearate: 1 part; silicone oil: 0.7 parts; silane coupling agent KH550: 1 part; magnesium oxide: 9 parts; boron nitride: 6 parts.
[0067] Application Example 2 Pretreatment of raw materials: Silica, aluminum hydroxide, zinc stannate, zinc borate, and glass fiber: Dry in an oven at 120°C for 4 hours to remove moisture and prevent it from affecting material properties.
[0068] TPE (thermoplastic elastomer): If it is in granular form, it can be used directly; if it is in block form, preheat it at 80°C to soften it, then cut it into small pieces for later use.
[0069] Magnesium oxide: Dry in an oven at 120°C for 4 hours to remove moisture.
[0070] Boron nitride: Ball milling is performed to reduce particle size, increase specific surface area, and improve its dispersibility in the matrix.
[0071] The method for preparing the protective shell for the automobile battery comprises the following steps: a. The dried silica, aluminum hydroxide, zinc stannate, zinc borate, glass fiber, magnesium oxide, boron nitride, TPE, polytetrafluoroethylene powder and the shielding composite material based on PPS composite carbon nanotubes obtained in Example 2 were added to a high-speed mixer, first stirred at 450 rpm for 3 min to make the materials preliminarily mixed, and then gradually increased the speed to 1100 rpm and continued stirring for 10 min; then, antioxidant 1010, antioxidant 1076, light stabilizer 770, light stabilizer 944, and anti-hydrolysis agent were added to the above mixture and stirred at a speed of 780 rpm for 5 min; b. Take silane coupling agent KH550, dilute it with ethanol, add it to the conductive carbon black, and ultrasonically treat it in an ultrasonic device for 30 minutes to make the silane coupling agent evenly coat the conductive carbon black. Then add it to the mixer and continue stirring for 3 minutes. Reduce the stirring speed to 800 rpm; then add zinc stearate and silicone oil, stir at a speed of 650 rpm for 3 minutes to make the materials mix more evenly.
[0072] c. The mixed materials were added into a twin-screw extruder for extrusion granulation. The temperatures of the extruder were set to 200°C, 260°C, 285°C, 300°C, 325°C, and 340°C from the feeding section to the die head, and the screw speed was 225 rpm. The extruded materials were air-cooled and pelletized to obtain composite material particles. d. The composite material particles were dried in an oven at 95°C for 4 hours and then added to an injection molding machine for injection molding to form a protective casing for automotive batteries; the injection molding temperature was 310°C, the injection molding pressure was 110 MPa, the holding time was 16 seconds, the cooling time was 30 seconds, and the mold temperature was controlled at 55°C.
[0073] Among them, the mass parts of each raw material used are: shielding composite material based on PPS composite carbon nanotubes: 70 parts; silicon dioxide: 5 parts; aluminum hydroxide: 8 parts; zinc stannate: 5 parts; zinc borate: 5 parts; TPE: 8 parts; antioxidant 1010: 0.8 parts; antioxidant 1076: 0.7 parts; light stabilizer 770: 0.8 parts; light stabilizer 944: 0.7 parts; conductive carbon black: 3 parts; glass fiber: 5 parts; polycarbodiimide Stabaxol~P: 1 part; polytetrafluoroethylene powder: 3 parts; zinc stearate: 1.5 parts; silicone oil: 1 part; silane coupling agent KH550: 1.5 parts; magnesium oxide: 10 parts; boron nitride: 8 parts.
[0074] Application Example 3 Pretreatment of raw materials: Silica, aluminum hydroxide, zinc stannate, zinc borate, and glass fiber: Dry in an oven at 100°C for 2 hours to remove moisture and prevent it from affecting material properties.
[0075] TPE (thermoplastic elastomer): If it is in granular form, it can be used directly; if it is in block form, preheat it at 60°C to soften it, then cut it into small pieces for later use.
[0076] Magnesium oxide: Dry in an oven at 100°C for 2 h to remove moisture.
[0077] Boron nitride: Ball milling is performed to reduce particle size, increase specific surface area, and improve its dispersibility in the matrix.
[0078] The method for preparing the protective shell for the automobile battery comprises the following steps: a. Add the dried silica, aluminum hydroxide, zinc stannate, zinc borate, glass fiber, magnesium oxide, boron nitride, TPE, polytetrafluoroethylene powder and the shielding composite material based on PPS composite carbon nanotubes obtained in Example 3 to a high-speed mixer, stir at 350 rpm for 2 min to make the materials preliminarily mixed, then gradually increase the speed to 900 rpm and continue stirring for 5 min; then, antioxidant 1010, antioxidant 1076, light stabilizer 770, light stabilizer 944, polycarbodiimide Stabaxol-P are added to the above mixture, and stir at a speed of 550 rpm for 3 min; b. Take silane coupling agent KH550, dilute it with ethanol, add it to the conductive carbon black, and ultrasonically treat it in an ultrasonic device for 25 minutes to make the silane coupling agent evenly coat the conductive carbon black. Then add it to the mixer and continue stirring for 3 minutes. Reduce the stirring speed to 650rpm; then add zinc stearate and silicone oil, stir at 450rpm for 2 minutes to make the materials mix more evenly.
[0079] c. The mixed materials were added into a twin-screw extruder for extrusion granulation. The temperatures of the extruder were set to 200°C, 245°C, 260°C, 285°C, 300°C, and 325°C from the feeding section to the die head, and the screw speed was 195 rpm. The extruded materials were air-cooled and pelletized to obtain composite material particles. d. The composite material particles were dried in an oven at 95°C for 4 hours and then added to an injection molding machine for injection molding to form a protective casing for automotive batteries; the injection molding temperature was 310°C, the injection molding pressure was 110 MPa, the holding time was 16 seconds, the cooling time was 30 seconds, and the mold temperature was controlled at 55°C.
[0080] Among them, the mass parts of each raw material used are: shielding composite material based on PPS composite carbon nanotubes: 50 parts; silicon dioxide: 3 parts; aluminum hydroxide: 5 parts; zinc stannate: 3 parts; zinc borate: 3 parts; TPE: 3 parts; antioxidant 1010: 0.3 parts; antioxidant 1076: 0.2 parts; light stabilizer 770: 0.3 parts; light stabilizer 944: 0.2 parts; conductive carbon black: 2 parts; glass fiber: 3 parts; polycarbodiimide Stabaxol~P: 0.5 parts; polytetrafluoroethylene powder: 1 part; zinc stearate: 0.5 parts; silicone oil: 0.5 parts; silane coupling agent KH550: 0.5 parts; magnesium oxide: 8 parts; boron nitride: 5 parts.
[0081] Application Comparative Example 1 Compared with Application Example 1, the difference is that magnesium oxide, zinc borate and zinc stearate are not added; the added amount of boron nitride is the sum of the masses of magnesium oxide and boron nitride in Application Example 1.
[0082] Application Comparative Example 2 Compared with Application Example 1, the difference is that silicon dioxide, zinc stannate and glass fiber are not added; the amount of aluminum hydroxide added is the sum of the masses of silicon dioxide and aluminum hydroxide in Application Example 1; the amount of zinc borate added is the sum of the masses of zinc stannate and zinc borate in Application Example 1.
[0083] Application Comparative Example 3 Compared with Application Example 2, the difference is that conductive carbon black and silane coupling agent KH550 are not added.
[0084] Application Comparative Example 4 Compared with Application Example 1, the difference is that TPE, antioxidant 1010 and light stabilizer 770 are not added; the addition amount of antioxidant 1076 is the sum of the masses of antioxidant 1010 and antioxidant 1076 in Application Example 1, and the addition amount of light stabilizer 944 is the sum of the masses of light stabilizer 770 and light stabilizer 944 in Application Example 1.
[0085] Application Comparative Example 5 Compared with Application Example 3, the difference is that the temperatures of the extruder from the feeding section to the die are set to 210°C, 270°C, 290°C, 310°C, 340°C, and 350°C in sequence, and the screw speed is 235rpm.
[0086] The experimental data obtained from Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.
[0087] The data obtained from Application Examples 1-3 and Application Comparative Examples 1-5 are shown in Table 2.
[0088] Table 1 Experimental data obtained from Examples 1-5 and Comparative Examples 1-3
[0089] As can be seen from Table 1, the shielding composite material based on PPS composite carbon nanotubes prepared by compounding a variety of raw materials in the present invention has good electrical insulation performance and high dielectric strength, and can effectively prevent current leakage; it has good shielding ability against electromagnetic interference, good flame retardant performance, high mechanical strength, and stable thermal performance.
[0090] Table 2 Data obtained from application examples 1-3 and application comparative examples 1-5
[0091] As can be seen from Table 2, the protective casing for automobile batteries prepared by the present invention further improves the performance of the main raw material (shielding composite material based on PPS composite carbon nanotubes) through the compounding of various raw materials. At the same time, the thermal conductivity and chemical corrosion resistance are greatly improved, and it is suitable for practical applications.
Claims
1. A method for preparing a shielding composite material based on PPS composite carbon nanotubes, characterized in that: The following steps are involved: (1) adding the acidified carbon nanotubes into the distilled purified NMP solvent, the mass concentration of the carbon nanotubes being 0.9-1.2%; then ultrasonically dispersing the carbon nanotubes, the ultrasonic power being 250-350 W, the ultrasonic time being 50-75 min, so that the carbon nanotubes form a uniform and stable dispersion in the NMP; in the ultrasonic process, intermittent ultrasonication is used; (2) Add the PPS product to the NMP dispersion of carbon nanotubes under stirring conditions. After the addition is completed, continue to stir the reaction in an oil bath at 75-80°C for 4-6 hours to dissolve the PPS and mix it with the carbon nanotubes. The stirring speed is 600-1200 rpm. Pour the evenly mixed solution into a mold, put it into a vacuum oven, and dry it at 95-105°C for 16-20 hours to remove the solvent NMP and solidify the PPS to obtain a shielding composite material based on PPS composite carbon nanotubes.
2. The method for preparing a shielding composite material based on PPS composite carbon nanotubes according to claim 1, characterized in that: The weight average molecular weight of the PPS product is 35,000 to 38,000, the degree of polymerization is 135 to 165, and the crystallinity is 35 to 45%; the mass of the carbon nanotubes is 4 to 7% of the mass of the PPS; in step (1), the intermittent ultrasonication is performed for 5 minutes and then paused for 2 minutes; in step (2), the addition rate of PPS is 0.5 to 1 g / s; during the drying process, a gradient vacuum is used: first, drying at 0.02 to 0.05 MPa for 8 to 10 hours, and then drying at 0.08 to 0.1 MPa for 8 to 10 hours.
3. The method for preparing a shielding composite material based on PPS composite carbon nanotubes according to claim 1, characterized in that: In the step (1), the acid treatment step of the carbon nanotubes is: ① Prepare mixed acid: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (2.5-3.0):1, and prepare 165-185 mL of mixed acid for every 1 g of carbon nanotubes; ② Stir the reaction at room temperature for 3 to 5 hours to allow the carbon nanotubes to contact the mixed acid and undergo an oxidation reaction; after the reaction is completed, pour the reaction solution into deionized water for dilution, and then filter to collect the solid product; ③ The solid product carbon nanotubes obtained by filtration are repeatedly washed with deionized water until the pH value of the filtrate is neutral to remove the residual acid; the washed carbon nanotubes are dried in a vacuum oven at 65 to 75° C. for 18 to 20 hours to obtain acidified carbon nanotubes.
4. The method for preparing a shielding composite material based on PPS composite carbon nanotubes according to claim 1, characterized in that: In the step (2), the preparation steps of the PPS product are as follows: Ⅰ. The reactor was replaced by nitrogen, and the vacuum was first evacuated to -0.08-0.1 MPa, and then nitrogen was introduced to 0.1-0.2 MPa, and this was repeated 3-5 times. Then, NMP solvent was added and stirring was started at a speed of 350-450 rpm. The stirring paddle was an anchor stirring paddle; Ⅱ. Add triethylamine to the reaction kettle, continue stirring, then add anhydrous sodium sulfide, p-dichlorobenzene, anhydrous sodium phosphate, sulfonate, yttrium oxide and tetrabutylammonium bromide in sequence; raise the temperature to 185-210°C at a rate of 1-2°C / min, keep reacting for 7-9h, and obtain a reaction solution; Ⅲ. The reaction solution obtained in step Ⅱ is added dropwise to the ethanol precipitant, the dropping speed is controlled at 1 to 2 mL / s, and the low-speed stirring is adopted at 50 to 100 rpm to precipitate PPS to form precipitated particles; Ⅳ. The precipitated particles obtained in step Ⅲ are first washed 2 to 3 times with an aqueous solution containing 0.2 to 0.3% by mass of disodium ethylenediaminetetraacetate, and then washed 5 to 8 times with deionized water to obtain PPS; the washed PPS is dried in a vacuum drying oven at 110 to 115° C. to constant weight to obtain a pure PPS product.
5. The method for preparing a shielding composite material based on PPS composite carbon nanotubes according to claim 4, characterized in that: The purity of the p-dichlorobenzene is above 99.5%, and the moisture content is lower than 0.05%; the purity of the anhydrous sodium sulfide is above 95%, and the molar ratio of the anhydrous sodium sulfide to p-dichlorobenzene is (1.05-1.15):
1.
6. The method for preparing a shielding composite material based on PPS composite carbon nanotubes according to claim 4, characterized in that: The amount of triethylamine used is 0.3% to 0.4% of the mass of p-dichlorobenzene; the amount of anhydrous sodium phosphate added is 0.15% to 0.25% of the mass of p-dichlorobenzene; the amount of sulfonate added is 0.6% to 0.8% of the mass of p-dichlorobenzene; the amount of yttrium oxide added is 0.06% to 0.08% of the mass of p-dichlorobenzene; the amount of tetrabutylammonium bromide added is 0.15% to 0.25% of the mass of p-dichlorobenzene; and the amount of NMP used is such that the total concentration of each substance in the reaction system is maintained at 38% to 43%.
7. A shielding composite material based on PPS composite carbon nanotubes, characterized in that: The shielding composite material is prepared by the preparation method of the PPS composite carbon nanotube-based shielding composite material according to any one of claims 1 to 6.
8. An application of the shielding composite material based on PPS composite carbon nanotubes according to claim 7, characterized in that: Used in protective casing for automotive batteries.
9. The use of the shielding composite material based on PPS composite carbon nanotubes according to claim 8, characterized in that: The method for preparing the protective shell for the automobile battery comprises the following steps: a. Add the dried silica, aluminum hydroxide, zinc stannate, zinc borate, glass fiber, magnesium oxide, boron nitride, TPE, polytetrafluoroethylene powder and PPS composite carbon nanotube-based shielding composite material to a high-speed mixer, first stir at 350-450 rpm for 2-3 min to make the materials preliminarily mixed, then gradually increase the speed to 900-1100 rpm, and continue stirring for 5-10 min; then, add antioxidant 1010, antioxidant 1076, light stabilizer 770, light stabilizer 944 and anti-hydrolysis agent to the above mixture, and stir at 550-780 rpm for 3-5 min; b. Take silane coupling agent KH550, dilute it with ethanol, add it to the conductive carbon black, ultrasonically treat it in an ultrasonic device for 25 to 30 minutes, then add it to the mixer, continue stirring for 2 to 3 minutes, and reduce the stirring speed to 650 to 800 rpm; then add zinc stearate and silicone oil, and stir at a speed of 450 to 650 rpm for 2 to 3 minutes; c. Add the mixed materials into a twin-screw extruder for extrusion granulation. The temperature of the extruder is set to 200°C, 245-260°C, 260-285°C, 285-300°C, 300-325°C, 325-340°C from the feeding section to the die. The screw speed is 195-225rpm. The extruded materials are air-cooled and then pelletized to obtain composite material particles. d. Dry the composite material particles in an oven at 85 to 95° C. for 2 to 4 hours, and then add them to an injection molding machine for injection molding to make a protective shell for automotive batteries; the injection molding temperature is 285 to 310° C., the injection molding pressure is 90 to 110 MPa, the holding time is 12 to 16 seconds, the cooling time is 22 to 30 seconds, and the temperature of the mold is controlled at 45 to 55° C.
10. The use of the shielding composite material based on PPS composite carbon nanotubes according to claim 9, characterized in that: In the preparation method of the protective shell for automobile batteries, the weight proportions of the raw materials used are: shielding composite material based on PPS composite carbon nanotubes: 50-70 parts; silicon dioxide: 3-5 parts; aluminum hydroxide: 5-8 parts; zinc stannate: 3-5 parts; zinc borate: 3-5 parts; TPE: 3-8 parts; antioxidant 1010: 0.3-0.8 parts; antioxidant 1076: 0.2-0.7 parts; light stabilizer 770: 0.3-0.8 parts; light stabilizer 944: 0.2-0.7 parts; conductive carbon black: 2-3 parts; glass fiber: 3-5 parts; anti-hydrolysis agent: 0.5-1 parts; polytetrafluoroethylene powder: 1-3 parts; Zinc stearate: 0.5-1.5 parts; Silicone oil: 0.5-1 parts; Silane coupling agent KH550: 0.5-1.5 parts; Magnesium oxide: 8-10 parts; Boron nitride: 5-8 parts.
Citation Information
Patent Citations
Electromagnetic shielding composite material for vehicle instrument and meter casing and preparation method thereof
CN108192315A
High-performance polyphenylene sulfide / polyamide electromagnetic shielding composite material and preparation method thereof
CN111849163A
Nano carbon material / PPS / elastomer composite material and preparation method thereof
CN112778760A
High-strength electromagnetic shielding shell and production process thereof
CN116622233A
Conductive polyphenylene sulfide composite material and preparation method thereof
CN118685035A
Cited By
Spraying-free polyphenylene sulfide composite material and application thereof in intake manifold
CN121628369A